THE JOURNEY OF ANNA BRADY FOR SEARCHING THE TRUE LOVE IN ANAND TUCKER'S LEAP YEAR (2010) MOVIE: A HUMANISTIC PSYCHOLOGICAL APPROACH - KUNCORO , DEDI RESTU (2011)
The major problem of this study is how the major character find the true love that reflected in Anand Tucker's Leap Year (2010) movie. The purpose of the research is to analyze the movie based on the structural elements and to analyze the movie based on the humanistic psychological perspective. The type of the research is qualitative. The primary data source that used by the writer is Leap Year (2010) movie directed by Anand Tucker and this script. Movie script was taken from a website. The secondary data are taken from the other sources that related to this movie such as biography of the author and the other relevant information. The method of collecting data is library research whereas the technique for analyzing is descriptive analysis. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis indicated that each of narrative and technical element is interrelated to each other. Secondly, based on the humanistic psychological depicted a girl who finds the true love after passing the great experience. According to Anna Brady, True love is to love someone more than the materials thing.